09 Linear Graphs: Review (4) 3-min Quiz (Responses)
 Share
The version of the browser you are using is no longer supported. Please upgrade to a supported browser.Dismiss

 
View only
 
 
ABCDEFGHI
1
TimestampNameReg noGroupLine a: Line b: Line c: Line d: Line e:
2
8/10/2015 17:50:32ANSWERS00y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
3
9/17/2015 12:39:35Rishita Subnavis71y = -0.5x - 2y = -0.5x + 3y = -0.5x + 3y = 4x - 2y - 4 = 0
4
9/17/2015 12:35:06Jerremy121y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
5
9/17/2015 12:37:01Loh Shao Cong151y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
6
9/17/2015 12:35:58
Marcus Tan Zheng Ning
171y = -0.5x - 2y = -0.5x + 3y = -0.5x - 2y = 4x - 2y - 4 = 0
7
9/17/2015 12:36:39tjin yao211y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
8
9/17/2015 12:34:00Yu Min Shen241y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
9
9/17/2015 12:44:24Yu Min Shen241y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
10
9/17/2015 12:39:36Celine Chow42y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
11
9/17/2015 12:41:08
Kho Hannah Gabrielle Chao
62y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
12
9/17/2015 12:35:20Alexander 82y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
13
9/17/2015 12:37:15Benedict Nai92y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
14
9/17/2015 12:36:16Dylan Lim142y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
15
9/17/2015 12:36:24yun kar kit252y = -0.5x + 3y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
16
9/17/2015 12:35:41Grace Cahyadi53y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
17
9/17/2015 12:35:27Kevin Fernandez113y = -0.5x - 2y = -0.5x + 3y = 4x - 2y = 4x - 2y - 4 = 0
18
9/17/2015 12:37:02Kh0r H513n K1t133y = -0.5x - 2y = -0.5x + 3y = 4x - 2y = 3x - 2y - 4 = 0
19
9/17/2015 12:40:42Malcolm Tan Qi En163y - 4 = 0y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
20
9/17/2015 12:38:39Vikhe Aryan Pramod223y - 4 = 0y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
21
9/17/2015 12:35:47yeo ming en233y - 4 = 0y = -0.5x + 3y = 4x - 2y = 3x - 2y - 4 = 0
22
9/17/2015 12:39:41Amanda Han Xin Hui24y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
23
9/17/2015 12:37:23Dylan Tan104y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
24
9/17/2015 12:41:51Ng Wen Bin, Justin184y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 4x - 2y - 4 = 0
25
9/17/2015 12:36:37Sim Choon Wee194y = -0.5x - 2y = -0.5x + 3y = -0.5x - 2y = 4x - 2y - 4 = 0
26
9/17/2015 12:38:16Tan Zi Bo204y = -0.5x - 2y = -0.5x + 3y = 3x - 2y = 3x - 2y - 4 = 0
27
Loading...
 
 
 
Form Responses 1